Susut Non Teknis Pada KWh Meter 1 Phasa d PT. PLN ULP Brebes - amanda husnul fadhilah (Jurnal Ilmiah Wahana Pendidikan, 2023)
In the distribution of electricity, there is a power loss factor or losses, a form of electrical energy loss that comes from the difference between the amount of electrical energy available and the amount of energy sold. One of the factors is non-technical shrinkage caused by the loss of electrical energy consumed by customers and non-customers because it is not recorded in sales which can cause illegal use, measurement errors on kWh meters, and electricity leakage in the power grid infrastructure. Utilization of electrical energy by customers served by PT PLN (Persero) from low voltage distribution networks to homes through APP (Limiting and Measuring Devices) where the device functions to measure and limit the electrical energy used by customers, limiting the use of electrical energy called MCB (Miniature Circuit Breaker) and measuring the use of electrical energy called kWh meter (Killo Watt Hour). Usage that is often misused such as kWh meter jammed, kWh meter minus, and Moving kWh meters to other parcels without PLN permission.